The Mechanisms by Which the Ketone Body D-β-Hydroxybutyrate May Improve the Multiple Cellular Pathologies of Parkinson's Disease - Norwitz, Nicholas G.; Hu, Michele T.; Clarke, Kieran (Frontiers in Nutrition, 2019)
Parkinson’s disease, a progressive neurodegenerative disorder characterized by motor and non-motor symptoms, is strongly associated with the death of dopaminergic neurons in the brain’s substantia nigra. Although dopamine replacement therapy temporarily helps patients manage their motor symptoms, this current standard of care fails to address the underlying network of pathologies that contribute to the persistent death of dopaminergic neurons. Thus, new treatment approaches are needed that address the underlying pathologies and, thereby, slow or halt the progression of the actual disease. D--hydroxybutyrate, a ketone body produced by the liver to support brain function during periods of starvation, may provide an option. Lifestyle interventions that induce endogenous D--hydroxybutyrate production, such as caloric restriction and ketogenic diets, are known to increase healthspan and lifespan in animal models and are used to treat neurological disorders. The efficacy of these interventions, along with the recent development of commercially available D--hydroxybutyrate-based nutritional supplements, should inspire interest in the possibility that D--hydroxybutyrate itself exerts neuroprotective effects. This review attempts to provide the molecular theory to justify further exploration of such a possibility. Herein, we explore the cellular mechanisms by which the ketone body, D--hydroxybutyrate, acting both as a metabolite and as a signaling molecule could, hypothetically, help to prevent the development or slow the progression of Parkinson’s disease. Specifically, the metabolism of D--hydroxybutyrate may help neurons replenish their depleted stores of ATP and protect neurons against oxidative damage. As a G-protein-coupled receptor ligand and histone deacetylase inhibitor, D--hydroxybutyrate may further protect neurons against energy deficit and oxidative stress, while also decreasing damaging neuroinflammation and death by apoptosis. Restricted to the available evidence, we largely provide a two-step logic to support our theory, drawing separately from the literature on the cellular effects of D--hydroxybutyrate and that on the pathogenesis of Parkinson’s disease. Future studies are needed to reveal whether D--hydroxybutyrate actually has the potential to serve as an adjunctive nutritional therapy that slows the progression of Parkinson’s disease.